2020
DOI: 10.1007/s00268-020-05512-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pediatric Resuscitation and Trauma Outcome (PRESTO) Model and Pediatric Trauma Scoring Systems in a Middle‐Income Country

Abstract: Background The pediatric resuscitation and trauma outcome (PRESTO) model was developed to aid comparisons of risk‐adjusted mortality after injury in low‐ and middle‐income countries (LMICs). We sought to validate PRESTO using data from a middle‐income country (MIC) trauma registry and compare its performance to the Pediatric Trauma Score (PTS), Revised Trauma Score, and pediatric age‐adjusted shock index (SIPA). Methods We included children (age < 15 years) admitted to a single trauma center in South Africa fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…This was also found in Traynor et al , who applied PRESTO to South African trauma data, and represents a strength of this scoring system for use in LMICs. 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was also found in Traynor et al , who applied PRESTO to South African trauma data, and represents a strength of this scoring system for use in LMICs. 7 …”
Section: Discussionmentioning
confidence: 99%
“…It was initially validated using the United States National Trauma Data Bank and has subsequently been validated in a middle-income setting (South Africa) and an LMIC setting (Rwanda). [5][6][7] In its application and validation in Rwanda, it was shown to be similarly effective in predicting child mortality as the Revised Trauma Score and Kampala Trauma Score, and to outperform the Kampala Trauma Score in children less than 5 years of age. 6 Due to PRESTO's success in both low-income 6 and middle-income 7 settings, and potential differences in causes, presentations and outcomes of specific childhood injuries in Tanzania, we sought to validate this scale in our population of paediatric injury patients at a tertiary zonal referral hospital in Northern Tanzania.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rate of injured children in our cohort was considerably high at 8.2%. In other pediatric registry studies, mortality rates ranged from 0.3% to 7.0% [ 3 , 9 , 12 , 29 , 32 ]. More specifically, a multi-site study at 10 centers in LMICs found an overall mortality rate of 0.8% for admitted pediatric injured patients [12] .…”
Section: Discussionmentioning
confidence: 99%